Ambient noise tomography of El Hierro island (Canary Islands) - Cabrera-Pérez, Iván; Soubestre, Jean; D’Auria, Luca; Przeor, Monika; García, Rubén; Barrancos, José; Padilla, Germán D.; Pérez, Nemesio M.; Prudencio, Janire (Frontiers in Earth Science, 2024)
To gain a deeper insight into the geological structure of El Hierro island, we employed Ambient Noise Tomography (ANT) to construct a 3D S-wave velocity model. We utilized data collected from a network of 21 broadband seismic stations, including permanent and temporary installations deployed on the island, during two survey campaigns conducted in 2015-2016 and 2021. This dataset allowed us to derive empirical Green's functions by cross-correlating signals from seismic ambient noise and to extract 105 dispersion curves through the Frequency-Time Analysis (FTAN) method. Subsequently, we generated 2-D maps of Rayleigh wave group velocities for periods ranging from 0.6 seconds to 2.7 seconds using a non-linear multiscale inversion technique.Finally, a Bayesian transdimensional approach was employed for depth inversion, creating a 3-D S-wave velocity model. Our investigation revealed the presence of seven significant seismic velocity anomalies. We identified two high-velocity anomalies located in the eastern and western parts of the island at a depth between 0 and 3 km below sea level (b.s.l.). We interpreted these anomalies as dense intrusive complexes of dikes, possibly linked to the Tanganasoga volcano and the formation of the Tiñor edifice. Additionally, we observed two high-velocity anomalies in the northern and southern parts of the island at a depth between 3 and 4 km b.s.l., which we related to the accumulation of solidified igneous rocks. On the other hand, a low-velocity anomaly was observed in the Golfo valley, between 0 and 0.5 km b.s.l., and we interpreted it as megalandslide deposits. Finally, two low-velocity anomalies were observed in the southern part of the island at different depths, between 0-0.5 km b.s.l. and 0-2 km b.s.l. These were interpreted as fractures generated by Quaternary volcanism along the SSE Rift.